Great mining and poverty from the poor: Las Bambas, Apurimac - Orco Diaz, Alipio (2020)
The investigation had three objectives; The first was to identify the variables that affect the self-perception of poverty of the residents of the Challhuahuacho district; then analyze the relationship of the displaced population and their self-perception of poverty; The third objective was to explore the possible contribution of the Las Bambas mining project to the subjective well-being of the local population. The research design was non-experimental and cross-sectional, descriptive correlational type. The study population was the heads of household, with a sample of three hundred and fifty, selected by simple probabilistic sampling. To collect the information, a questionnaire referring to personal information, the environment and the level of satisfaction in various domains of life was applied. The results obtained for the first objective show that the variables: education, displacement, health satisfaction, job satisfaction, satisfaction with family income and satisfaction in maintaining dependents adequately; significantly affect the subjective poverty of the residents of Challhuahuacho. Regarding the second objective, it is evident that there is a significant inverse relationship between subjective poverty and the condition of being displaced. Finally, according to the results, the Las Bambas mining project contributes little to subjective well-being. JEL: I31, I32, I38.